Pengaruh Cash Holding, Firm Size, Profitability, Dan Financial Leverage Terhadap Income Smoothing - Devina Elfita Adiwidjaja, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study aims to analyze the correlation between cash holding, firm size, profitability, and financial leverage to income smoothing on property, real estate, and building construction firms in Indonesia Stock Exchange in the study period of 2015-2017. There are 64 listed property, real estate, dan building construction companies. The sample selection uses a purposive sampling technique and produces a total sample of 40 companies. The analysis in this study is a logistic regression analysis. This study gives the result that cash holding has a positive and not significant effect on income smoothing, firm size and profitability have a positive and significant effect on income smoothing, and financial leverage has a negative and not significant effect on income smoothing